Konstitusionalisasi Perlindungan Konsumen Perspektif Hukum Hak Asasi Manusia dan Hukum Profetik Islam - Musataklima, Musataklima; Syamsudin, M; Sulistiyono, Adi (Jurnal HAM, 2023)
People are ipso facto consumers. People, as consumers, have rights that must be protected by law. As human beings, consumers have rights that must be protected, respected, fulfilled, and advanced by the state. However, current consumer protection could be more effective and stronger, as evidenced by many consumer complaints to the National Consumer Protection Agency. (BPKN). This is also due to the weak legal instruments of consumer protection that need to be burned into the country’s constitution. Based on this, the study aims to analyze the urgency of constitutionalizing consumer protection from the perspective of human rights and prophetic Islamic law. The research method used is the study of doctrinal law with conceptual and legislative approaches. The data used is secondary data, i.e., primary, secondary, and tertiary legal materials obtained through the study of libraries and online searching (internet searching), surfing, and downloading, and subsequently analysed qualitatively. As for the results of this study, the first constitutionalization of consumer protection from a human rights perspective can guarantee the fulfillment of the right to life as a fundamental human right and can be an instrumentation of the fulfillment of a right to a decent and safe standard of living to be consumed. Second, from the perspective of prophetic law, the constitutionalization of protection can empower public authorities to fulfill, respect, implement, and enforce consumer protection, thus realizing the liberation and humanization of consumers from unfair and fraudulent trade.